Walking on the rope: Asian Community in London - Antipina-Turner, Ekaterina (project baikal, 2017)
The article presents a survey of the history and relationships of migrants from the South Asia and China in Britain. Their competitive character is underlined. The Chinese diaspora is regarded as a relatively isolated community with high educational and social requests. A review of public sources allows making a conclusion about the desire of the Chinese youth for assimilation and, at the same time, exists the opposite tendency to preserve the national identity.